2016
DOI: 10.1080/07420528.2016.1225074
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythm in QT interval is preserved in mice deficient of potassium channel interacting protein 2

Abstract: Potassium Channel Interacting Protein 2 (KChIP2) is suggested to be responsible for the circadian rhythm in repolarization duration, ventricular arrhythmias, and sudden cardiac death. We investigated the hypothesis that there is no circadian rhythm in QT interval in the absence of KChIP2. Implanted telemetric devices recorded electrocardiogram continuously for 5 days in conscious wild-type mice (WT, n = 9) and KChIP2 mice (n = 9) in light:dark periods and in complete darkness. QT intervals were determined from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…We have previously documented the presence of a 24‐h rhythm of the QRS complex in conscious wild‐type mice (Gottlieb et al. ). The control mechanism of such 24‐h rhythm can reside in (1) the endogenous cardiac clock, using a transcription‐based mechanism (Martino and Young ); (2) an endogenous clock of another cell type or organ that provides a neurohumoral signal to the heart; or (3) by the central clock in the suprachiasmatic nucleus of the brain, where environmental cues entrain the master clock controlling all the peripheral organ clocks (Buhr et al.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…We have previously documented the presence of a 24‐h rhythm of the QRS complex in conscious wild‐type mice (Gottlieb et al. ). The control mechanism of such 24‐h rhythm can reside in (1) the endogenous cardiac clock, using a transcription‐based mechanism (Martino and Young ); (2) an endogenous clock of another cell type or organ that provides a neurohumoral signal to the heart; or (3) by the central clock in the suprachiasmatic nucleus of the brain, where environmental cues entrain the master clock controlling all the peripheral organ clocks (Buhr et al.…”
Section: Discussionmentioning
confidence: 97%
“…Radiotransmitter telemetry devices (ETA‐F10, Data Sciences International, St. Paul, MN) were implanted in anesthetized mice (2% isoflurane in 100% O 2 ) subcutaneously on the dorsal area between the scapulae, as previously described (Gottlieb et al. ). Postoperative analgesia included carprofen (10 mg/kg, s.c.), lidocaine, and bupivacain (0.4 and 1.0 mg/kg, respectively, in the s.c. pocket).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A subcutaneous pocket was created in the mid‐dorsal region and the telemetric device was placed inside. The electrode leads were tunnelled subcutaneously to the right shoulder joint (negative lead) and under the left armpit (positive lead) and secured using non‐absorbable suture (Ethicon), creating a lead‐II ECG with a high signal‐to‐noise ratio . In a subset of db/db mice, blood pressure in the abdominal aorta was recorded simultaneously with the ECG (HD‐X11; DataSciences International) as previously described .…”
Section: Methodsmentioning
confidence: 99%
“…Jeyaraj et al [29] showed that Kruppel-like factor 15 (Klf15) is a CCG that directly regulates KChIP2 expression, and that deletion of Klf15 abolishes the circadian rhythm in QT interval and increases suspectibility of mice to ventricular arrhythmias. However, Gottlieb et al [23] concluded that KChIP2 is not a mechanistic link between the cardiac circadian clock and ventricular repolarization and arrhythmogenesis, based on their finding that KChIP2-deficient mice still have a circadian rhythm in QT interval. Rather, they suggest that Klf15 expression controls the transcription of other genes responsible for the circadian rhythm in repolarization and susceptibility to arrhythmias.…”
Section: Circadian Transcription Of Cardiac Ion Channelsmentioning
confidence: 99%